MANAGEMENT OF SUSTAINABLE DEVELOPMENT OF OIL AND GAS PRODUCING REGION - KORIAKINA, Elena Anatolievna; KULAKOVA, Nadezhda Sergeevna (Journal of Environmental Management and Tourism; Vol 6 No 2 (2015): JEMT Volume VI Issue 2(12) Winter 2015, 2016)
The work demonstrates the dynamics of the world market of energy commodities. It shows the role of the fuel and energy sector as an element of the system of the country’s economy development and basis of the profitable part of the Russian budget. The authors of the article understand the sustainable development of the region as a decrease in the territory dependence on the situation on the global energy market, increase in competitiveness in the world market of hydrocarbon processing and agriculture. Development and implementation of investment projects in the region in the framework of the processing innovative technologies will reduce the region's dependence on commodity proceeds, and increase in the number of the budget revenue sources will reduce the degree of its vulnerability to market conditions in a single market. It explains the influence of the Tyumen Region on the sustainable development of the country. In order to develop management solutions related to the vector of regional development, the authors have adapted the model of the comprehensive estimation of regional sustainable development based on the improved system of indicators. The authors chose the oil and gas producing region – the Tyumen Region (Russia) – as the object of the study, conducted an analysis based on the selected inductors, which allowed to identify problems and propose measures that would promote the development of both the region and Russia as a whole in result. It provides the complex of ways to manage sustainable development of an oil and gas producing region under the current conditions, among which the authors highlight: optimization of the tax climate for investors and enterprises funding the processing sector and advanced technologies; tax relief to the newly open and modernized enterprises; state co-financing of industrial enterprises serving oil and gas sector and hydrocarbon processing enterprises; reorientation of the labor force.
Keywords: Market of energy commodities; fuel and energy sector; sustainable development of region; gross domestic product; innovational technologies; investment projects